Development of mesoporous titanium dioxide hybrid poly(vinylidene fluoride) ultrafiltration membranes with photocatalytic properties. Issue 19 (27th January 2016) - Zhao, Jianquan; Liao, Chanjuan; Liu, Jing; Shen, Xinyu; Tong, Hua
ABSTRACT: A photocatalytic activity ultrafiltration membrane (UFM) was prepared by the blending of a poly(vinylidene fluoride) (PVDF) polymer with mesoporous titanium dioxide (M‐TiO2 ) particles via the phase‐inversion method. The microstructure of the membrane and Ti element distribution were characterized by scanning electron microscopy and energy‐dispersive X‐ray spectroscopy. Their properties were also determined by thermogravimetric analysis, differential scanning calorimetry, Fourier transform infrared spectroscopy, tensile stress tests, contact angle tests, bovine serum albumin retention, water flux, and permeation flux. When the M‐TiO2 concentration reached 1 wt %, the thermal stability, mechanical properties, hydrophilicity, flux, and antifouling performance of the M‐TiO2 /PVDF UFM were improved to an optimal value with the M‐TiO2 particles successfully entrapped and evenly distributed throughout the PVDF polymer matrix. Compared with the P25‐modified PVDF UFM (1 wt %), the M‐TiO2 ‐modified PVDF UFM (1 wt %) exhibited better photocatalytic activity and wonderful stability in the UV photocatalytic degradation of the organic dye Rhodamine B. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43427. Abstract :